2013
DOI: 10.1007/s00436-013-3334-2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of dendritic cell apoptosis by Leishmania mexicana amastigotes

Abstract: Macrophages (Mφ) and dendritic cells are the major target cell populations of the obligate intracellular parasite Leishmania. Inhibition of host cell apoptosis is a strategy employed by multiple pathogens to ensure their survival in the infected cell. Leishmania promastigotes have been shown to protect Mφ, neutrophils, and dendritic cells from both natural and induced apoptosis. Nevertheless, the effect of the infection with Leishmania amastigotes in the apoptosis of these cell populations has not been establi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 39 publications
1
20
0
4
Order By: Relevance
“…Figure b shows the mean ± SD of three independent experiments. We have previously demonstrated that the infection of moDC with L. mexicana amastigotes diminishes camptothecin‐induced DNA fragmentation . Taking this result in account, in this work we inhibited p38 and JNK in moDC previously to the infection with L. mexicana amastigotes and treatment with camptothecin in order to determine the participation of p38 and JNK in the fragmentation of DNA.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Figure b shows the mean ± SD of three independent experiments. We have previously demonstrated that the infection of moDC with L. mexicana amastigotes diminishes camptothecin‐induced DNA fragmentation . Taking this result in account, in this work we inhibited p38 and JNK in moDC previously to the infection with L. mexicana amastigotes and treatment with camptothecin in order to determine the participation of p38 and JNK in the fragmentation of DNA.…”
Section: Resultsmentioning
confidence: 84%
“…One cell‐mediated defense mechanism that Leishmania affects in behalf of its survival is apoptosis. It has been widely described that Leishmania inhibits apoptosis in various cell types including macrophages , monocytes , neutrophils and dendritic cells . Nevertheless, the pathways that are targeted by the parasite to achieve the anti apoptotic effect have not been fully addressed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, an intrinsic ability to delay apoptosis induction in various cell subsets, including macrophages, mo‐DCs and polymorphonuclear neutrophil granulocytes, has been described for promastigotes and amastigotes of several Leishmania spp. , supporting the speculation that the Leishmania parasite may deliberately manipulate host cell apoptotic machinery to improve its survival and pathogenicity. This activity, however, arose when cells were challenged with a pathogen multiplicity equal to or lower than 10 parasites per cell, disregarding the potential cytotoxic effect that higher parasite numbers may display.…”
Section: Discussionmentioning
confidence: 75%
“…Estos resultados coinciden con observaciones previas, en las cuales la infección con promastigotes de L. major, L. donovani o L. amazonensis inhibe la apoptosis en macrófagos y otras células hospederas (131-133, 207, 236). La infección con promastigotes de L. major inhibe la apoptosis espontánea de los neutrófilos (207), y la infección con promastigotes y amastigotes de L. mexicana inhibe la apoptosis de células dendríticas (135,136). Se sabe que los neutrófilos son reclutados al sitio de la infección y estos son muy eficientes para internalizar parásitos.…”
Section: Acción De Espisulosina En Promastigotes De L Panamensisunclassified